What do We Know about Tourism Cluster and Insular Economy: A Bibliometric Study - J. Teixeira, Sérgio; J. M. Ferreira, João; C. Correia, Ricardo (Journal of Tourism, Sustainability and Well-being, 2020)
The tourism cluster is certainly a key sector study for any mainland or island economy. The paper reviews the extent and emerging perspectives on and approaches to tourism cluster and island economy. We adopted a systematic literature review using a bibliometric approach, focusing on the creation of maps and networks of visualization of intellectual structure in the period of 30 years (1987-2017), through the Web of Science database. The authors identify and classify the various theoretical lenses in the domain of cluster tourism and insular economy and suggest the future research agenda. The paper contributes by conceptually categorizing and mapping the extant research into five groups of clusters or approaches to the tourism cluster and insular economy: i) impacts; ii) islands; iii) satisfaction; iv) insularity, and v) tourism. The authors argue that tourism is undoubtedly the sector linked to island regions and that is an engine of the economy of an island.